Sistema de gestión ambiental de los residuos sólidos hospitalarios en el hospital II – I de Moyobamba - Cotrina Malpartida, Ketty Majail (2010)
By knowing the current management of solid hospital waste Hospital MINSA Moyobamba II-I, bom out the problem and the interest in developing the project "Environmental Management System Hospital Hospital Solid Waste II-I MINSA Moyobamba, located Moyobamba in the district, province of Moyobamba, department of San Martin, and general aims: to develop a proposal by the Environmental Management of Solid Waste II Hospital Hospital-! Moyobamba, and as specific objectives: • Conducta situational analysis ofhospital solid waste generated by the hospital II.-I Moyobamba. o Making the diagnosis allowed us to leam about the management of solid waste management and hospital and concluded that there is inadequate data were limited allocation of financia! resources and personnel for the good management in terms of poor management is beginning to train staff not they work and the general public attending the hospital, so would improve the organizational, operational and technical environment. • Determine the classification and characterization of hospital solid waste generated by each serví ce area of Hospital II-I Moyobamba. o By the classification and characterization we have to know the amount and type of solid waste that is generated by service or area in the hospital, likewise through a detailed study we obtained the daily population (workers, patients, visitors, etc.). in order to obtain the daily PPC is 37,784 kg 1 Pac 1 da y. • Determine the critical points of environmental management in the Hospital II-I Moyobamba. o Critical points 1s determined from the organizational, technical, operational, until the environmental aspect. xiv • Designa proposed Environmental Management System Hospital Solid Waste III Hospital MINSA Moyobamba. o The design of the proposal put forward was made with the purpose of contributing towards improving the environmental management of solid hospital waste Hospital II-I MINSA Moyobamba. o Y to ensure the safety of staff is in direct contact with solid waste and other persons who frequent the hospital and community.